GAME SEJARAH UMRI SEBAGAI MEDIA PENGENALAN UMRI BERBASIS ANDROID - Harun Mukhtar; Jum’atul Zikri; Mitra Unik (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2021)
Muhammadiyah Riau University (UMRI) is one of private University on Riau – Pekanbaru. A University which is one of the business charities of Muhammadiyah Indonesia. To maintain the historical value of UMRI requires an interesting media to keep Umri citizen in particular keep in mind the history of UMRI development. for that made an interactive game that is able to tell the history of development of UMRI. In the development of this game used MDLC as a method in the development of interactive games. For the development of this game is used Unity as Game editor. With this game the history of UMRI development can be known by the public.